Complex meiotic configuration of the holocentric chromosomes: the intriguing case of the scorpion Tityus bahiensis - Schneider, Marielle Cristina; Zacaro, Adilson Ariza; Pinto-da-Rocha, Ricardo; Candido, Denise Maria; Cella, Doralice Maria [UNESP] (Springer, 2009)
Mitotic and meiotic chromosomes of Tityus bahiensis were investigated using light (LM) and transmission electron microscopy (TEM) to determine the chromosomal characteristics and disclose the mechanisms responsible for intraspecific variability in chromosome number and for the presence of complex chromosome association during meiosis. This species is endemic to Brazilian fauna and belongs to the family Buthidae, which is considered phylogenetically basal within the order Scorpiones. In the sample examined, four sympatric and distinct diploid numbers were observed: 2n = 5, 2n = 6, 2n = 9, and 2 = 10. The origin of this remarkable chromosome variability was attributed to chromosome fissions and/or fusions, considering that the decrease in chromosome number was concomitant with the increase in chromosome size and vice versa. The LM and TEM analyses showed the presence of chromosomes without localised centromere, the lack of chiasmata and recombination nodules in male meiosis, and two nucleolar organiser regions carrier chromosomes. Furthermore, male prophase I cells revealed multivalent chromosome associations and/or unsynapsed or distinctly associated chromosome regions (gaps, less-condensed chromatin, or loop-like structure) that were continuous with synapsed chromosome segments. All these data permitted us to suggest that the chromosomal rearrangements of T. bahiensis occurred in a heterozygous state. A combination of various factors, such as correct disjunction and balanced segregation of the chromosomes involved in complex meiotic pairing, system of achiasmate meiosis, holocentric nature of the chromosomes, population structure, and species dispersion patterns, could have contributed to the high level of chromosome rearrangements present in T. bahiensis.
Keywords: achiasmate meiosis; cytogenetic; diploid number; nucleolar material; synaptonemal complex